â€œTHERMAL CONDITIONINGâ€ UNTUK MENGURANGI DAMPAK PANAS PADA PAKAIAN DENGAN KOMBINASI WARNA - Husna Noor Mufida; Muh Syukri Ahsani; Mahardika Prasetya Aji; Sulhadi Sulhadi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Brightly colored clothing at the time the sun is hot compared using dark-colored clothing, this is because the color effect on the emissivity. Therefore, research that aims to find a good color combination to reduce the impact of heat on clothing. The independent variables in this study is a combination of colors and the dependent variable is the change in temperature. The colors used in this study there are five, namely black, white, red, green, blue. The study was conducted by measuring the temperature inside and outside the box. Furthermore, the data has been analyzed by the analysis table using Microsoft Excel. Based on the analysis, we concluded that the best color combinations to reduce the impact of heat on the clothes is the color white in output and color in the color blue and white output and color in green. While the colors were very bad in reducing the impact of heat on the clothes are the output colors in black and red. Keywords: Color Combination, Heat, Thermal conductivity.